Protective Application of Chinese Herbal Compounds and Formulae in Intestinal Inflammation in Humans and Animals - Yang Yang; Gang Xiao; Pi Cheng; Jianguo Zeng; Yisong Liu (Molecules, 2023)
Intestinal inflammation is a chronic gastrointestinal disorder with uncertain pathophysiology and causation that has significantly impacted both the physical and mental health of both people and animals. An increasing body of research has demonstrated the critical role of cellular signaling pathways in initiating and managing intestinal inflammation. This review focuses on the interactions of three cellular signaling pathways (TLR4/NF-κB, PI3K-AKT, MAPKs) with immunity and gut microbiota to explain the possible pathogenesis of intestinal inflammation. Traditional medicinal drugs frequently have drawbacks and negative side effects. This paper also summarizes the pharmacological mechanism and application of Chinese herbal compounds (Berberine, Sanguinarine, Astragalus polysaccharide, Curcumin, and Cannabinoids) and formulae (Wumei Wan, Gegen-Qinlian decoction, Banxia xiexin decoction) against intestinal inflammation. We show that the herbal compounds and formulae may influence the interactions among cell signaling pathways, immune function, and gut microbiota in humans and animals, exerting their immunomodulatory capacity and anti-inflammatory and antimicrobial effects. This demonstrates their strong potential to improve gut inflammation. We aim to promote herbal medicine and apply it to multispecies animals to achieve better health.